STUDI KARAKTERISTIK SEDIMEN KAITANNYA DENGAN PENGELOLAAN WILAYAH PESISIR INDRAMAYU JAWA BARAT - Basri M Ganie (BPPT)
The northern part of java coastline in particular in Dadap Valley and Limbangannearby to Indramayu was heavily destroyed by erosion affected by strong wavecoming from opensea.It showed that some areas such as in Pamanukan coastline seemed to be heavily threated by erosion.Â This study was carried out by scientist of BPPT with the Objective of understanding the characteristic of sediments affected by erosion in Indramayu coast areas. According to information from local people living nearby coast and beach of Indramayu, The erosion destroyed coastline approximately 10-20 meter every year. Based on grain size analysis the sediments reveald 3 catagories of environment covered a long coast areas in Indramayu as follow :1. Coast sediments ; consisting of fein coastal sand, Silt.2. Delta sediments ; Siltig sand with Mollusca fragments.3. Flood upland sediments; Humous clay, silt, middle to coarse sands.The Occurrence of fein sand sediment deposition on the upper layer of coastalareas indicated that areas may influenced directly also with strong long shorecurrent.Keywords: sediment characteristic, coast, delta sediments, flood upland sediments, Delta , sediment abrasion